A U.S. Food and Drug Administration perspective on cannabis research and drug development - Cassandra L. Taylor; Schuyler A. Pruyn (Open Exploration Publishing Inc., 2023)
Since the early 1970s, the U.S. Food and Drug Administration (FDA) has received over 800 investigational new drug applications (INDs) for, and pre-INDs pertaining to, research of cannabis or cannabis-derived products. The current data show that applications for research of these products submitted by both academic researchers and commercial developers focus on four major clinical areas: addiction and pain medicine (53%), neurology (19%), immunology and inflammation (14%), and psychiatry (9%). The product types studied have expanded greatly in recent years and include a wide variety of topical, inhalable, injectable, and oral products. In this article, the authors present a breakdown of cannabis and cannabis-derived applications received by the FDA over the past 50 years. The authors also provide a summary of their experience and challenges in reviewing applications for research of cannabis and cannabis-derived products, as well as recommendations for those interested in studying cannabis and cannabis-derived products in human clinical trials. This perspective article includes a discussion on important IND criteria, the pre-IND consultation program, drug master files (DMFs), and various guidance documents and resources. Lastly, the authors provide their perspective for the future of cannabis drug development.